Incentive proposals for electric vehicles in the Spanish tax system - Moreno Inocencio, Ángel (Cívitas Thomson Reuters, 2025)
The chapter discusses various tax incentives designed to encourage the adoption of electric vehicles (EVs) as part of global efforts to reduce carbon emissions and combat climate change. Different types of tax benefits are described, including purchase subsidies, discounts, and exemptions from sales taxes or registration fees. The chapter also examines tax credits for EV manufacturers to stimulate production, as well as tax incentives for EV manufacturers. Additionally, the chapter highlights the impact of these incentives on the electric vehicle market, emphasizing their role in reducing the initial cost of purchasing electric vehicles, which can be a barrier for many consumers. It also addresses the long-term benefits of reduced operating and maintenance costs for electric vehicle owners, and how these tax policies align with broader environmental policies. The chapter also discusses the potential challenges and limitations of such policies, such as dependence on government budgets and the need for continuous innovation in charging infrastructure. The effectiveness of these incentives in relation to achieving sustainable growth in the electricity sector is also analyzed.
Keywords: electric car; mobility; taxes incentives